2020
DOI: 10.3389/fsufs.2020.00006
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Occurrence and Agricultural Importance of Beauveria bassiana and Metarhizium anisopliae

Abstract: Entomopathogenic fungi are often relied on as important components of integrated pest management in tropical agriculture, either as biopesticides or as naturally occurring microbes conserved in the environment. Tropical abiotic conditions are often well-suited for microbial growth, and tropical habitats can be teeming with microbial biodiversity. However, competitive interactions with other fungi and the need to overcome defenses of hosts adapted to high fungal loads may inhibit the ability of insect pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 102 publications
0
25
0
5
Order By: Relevance
“…Fungi are the predominant natural pathogens of arthropods [ 1 ]. Hypocrealean entomopathogenic fungi (EPF), such as those in the genera Beauveria and Metarhizium , are natural inhabitants of most terrestrial ecosystems, including natural and agricultural areas [ 2 , 3 , 4 ]. EPF can interact with arthropod hosts as parasites or saprophytes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi are the predominant natural pathogens of arthropods [ 1 ]. Hypocrealean entomopathogenic fungi (EPF), such as those in the genera Beauveria and Metarhizium , are natural inhabitants of most terrestrial ecosystems, including natural and agricultural areas [ 2 , 3 , 4 ]. EPF can interact with arthropod hosts as parasites or saprophytes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarks: Mean values ± SE within a similar column and treatments followed by the same letters are not significantly different at p < 0.01 based on HSD test. AM 0 : without mycorrhizae, AM 1 : mycorrhizae 5 g per plant, AM 2 : mycorrhizae 10 g per plant, Bb 1: B. bassiana application every 10 days, Bb 2: B. bassiana application each 5 days B. bassiana is one of the most effective entomopathogens against some group of pests including the leafminers (Devi, Padmavathi, Rao, Khan, & Mohan, 2008;McGuire & Northfield, 2020;Migiro, Maniania, Chabi-Olaye, & Vandenberg, 2010;Saleh, Anshary, & Made, 2018) but some factors such as the application technique and persistence, determined their efficacy in the fields (Jaronski, 2010). Our study revealed that 5 days interval application of B. bassiana is more effective in suppressing population and infestation of the shallots leafminer compared to 10 days interval.…”
Section: Effect Of Beauveria Application On Leaf Miners and Shallotmentioning
confidence: 99%
“…Air temperature and humidity were also reported determining the efficacy of B. bassiana against lesser grain borer, Rhyzopertha dominica (Zaman et al, 2020). Therefore the environmental effect should be considered when planning an integrated pest management strategy based on the application of entomopathogenic fungi such as B. bassiana and M. anisopliae (McGuire & Northfield, 2020). Both entomopathogenic fungi have high pathogenicity against leafminers of pea bean (Migiro, Maniania, Chabi-Olaye, & Vandenberg, 2010), common bean, Phaseolus vulgaris (Gathage et al, 2016), and major pests of vegetable legumes and brassicas (Srinivasan, Sevgan, Ekesi, & Tamò, 2019).…”
Section: Effect Of Beauveria Application On Leaf Miners and Shallotmentioning
confidence: 99%
“…Beauveria, Metarhizium and Isaria genera are listed among the most important microbial species which are used as biological control agents and which have been documented to act against a wide range of insect hosts [10,[17][18][19][20]. The fungal species which have been the most studied for their action against stored product insect pests and which have produced promising results are Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Cordycipitaceae), Metarhizium anisopliae (Metschinkoff) Sorokin (Hypocreales: Clavicipitaceae) and Isaria fumosorosea Wize (Hypocreales: Clavicipitaceae) [9,[21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%